Polish Insurance Market Compared to Selected European Countries in the Years 2000-2010 - Witkowska, Justyna (Olsztyn Economic Journal, 2012)
This paper presents the insurance market in Poland and selected European countries. The most important parameters characterising this segment of the financial market were used. The premiums written, population and GDP were analysed to outline the major changes occurring among the insurers operating in Poland and the CEA1 member countries.